Tentacles, Blocks and Axes: Space Syntax Applied to the Study of Urban Growth in Aracaju/SE - Martins de Carvalho, Lina (2024)
Dispersed urban growth resulting from political and economic interests causes significant socio-environmental damage. Based on this premise, the objective of this work is to understand the urban growth process of Aracaju, capital of the state of Sergipe (Brazil), read from a morphological/configurational perspective, and discuss its implications for society. As methodological instruments, subsidies from urban history were compared with the diachronic configurational modeling of the municipality and the metropolitan region, produced according to Space Syntax (Theory of the Social Logic of Space). As a result, it was observed that the city presents, throughout its existence, two distinct configurations of urban fabric: compact, connected, orthogonal central areas with a high level of global integration; and, linear peripheral zones (North and South), with dispersed occupation, fragmented and with low accessibility, coming from “urban blocks” with low levels of global integration, surrounded by open spaces.